Contos de Fadas e Casamento na Prosa Romântica de José de Alencar - Brasil, Francisca Patrícia Pompeu (2007)
This essay is aimed at assessing the causes through which some of José de Alencar’s romantic romances made use of the discourse of fairy tales to convey an idea of marriage. The following fairy tales Cinderella, Snow White and the Beauty and the beast by the Grimm brothers, were chosen for this purpose. Among José de Alencar’s masterpieces, we have opted to work with those, that could be compared to the fairy tales aforementioned. They are as follows: A Pata da Gazela, O Tronco do Ipê, A Viuvinha, Cinco Minutos, Til,O Guarani, Lucíola and Senhora. From this standpoint, these narratives, the reading practice worked as a tool for marriage; we assume that such instruction was first and foremost directed toward woman. Throughout our research we came to recognize that romantic discourse present in such stories sought to legitimize and justify the values nurtured by burgeoise. Among them we point out praise of family bedrock and the importance given to affection.